NERACA AIR DI PERKEBUNAN KELAPA SAWIT DI PPKS SUB UNIT KALIANTA KABUN RIAU - Heriansyah Pasaribu; Aras Mulyadi; Suardi Tarumun (Program Pascasarjana Universitas Riau, 2012)
The water system disruption caused by the oil palm has become the issue of the environment. Oil palm plantations rated as the cause of changes in groundwater conditions, for allegedlyusing so much water for growth and production. To clarify these issues will require researchto provide an overview of changes in the water table of oil palm plantations in terms of thewater balance of oil palm plantations. The result showed that the calculation of thepercentage of interception in stands of oil palm has a value of 21.23% of the rainfall. Evapotranspiration in palm oil plantations ranged 68.23-125.63 mm/month, with an averageof 92.05 mm/month or 1104.5 mm/year. The water requirement of oil palm plantations issmaller when compared to the water needs of coconut trees and forest plants such as pine,acacia, segon, rubber and teak.